Pola Asuh Orang Tua dan Dampaknya terhadap Perilaku Anak: Studi Kasus di Gampong Meunasah Dayah Meunara Kecamatan Kutamakmur, Aceh Utara - Nurainiah, Nurainiah (Pase: Journal of Contemporary Islamic Education, 2023)
Behavior is the way a person acts as a reaction to the characteristics and circumstances experienced. Children's behavior is influenced by how parents provide care in their daily lives. The impact of parental care determines the behavior exhibited by the child. This research aims to determine parental parenting patterns and their impact on children's behavior in Gampong Meunasah Dayah Meunara, Kutamakmur District, North Aceh Regency. The research method used is a descriptive qualitative method. Meanwhile, data collection techniques are carried out through observation, interviews, and documentation. Meanwhile, for data analysis techniques, researchers use data reduction, data presentation, and conclusion/verification. The research results show that the parenting styles used by parents in educating, developing, and guiding their children include authoritarian, democratic, permissive, and neglectful. However, parents predominantly use permissive and neglectful parenting styles. The impact of the parenting style used by parents on the behavior of their children in Gampong Meunasah Dayah Meunara, Kutamakmur District, North Aceh Regency is that they become rebellious, angry, lazy, and difficult to accept advice, while some can still be coached and guided.